2019
DOI: 10.1080/08870446.2019.1609678
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement inductions influence health behaviour: the working memory account of persuasion

Abstract: Objective: Because the working memory (WM) has a limited capacity, the cognitive reactions towards persuasive information in the WM might be disturbed by taxing it by other means, in this study, by inducing voluntary eye movements (EMi). This is expected to influence persuasion. Methods: Participants (N ¼ 127) listened to an auditory persuasive message on fruit and vegetable consumption, that was either framed positively or negatively. Half of them was asked to keep following a regularly moving dot on their sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
0
10
1
Order By: Relevance
“…The latter formulation only implies the negative outcomes, and focuses on the solution, thereby lowering the threat and the risk of defensive reactions. However, one earlier study on EMi showed that such message framing did not make a difference in persuasion regarding fruit and vegetable consumption (Dijkstra & Elbert, 2019). Secondly, when prevention efforts focus on lowering SMU, then those with high SMU scores should be targeted, and according to the present study, these are not particularly defensive towards this message.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The latter formulation only implies the negative outcomes, and focuses on the solution, thereby lowering the threat and the risk of defensive reactions. However, one earlier study on EMi showed that such message framing did not make a difference in persuasion regarding fruit and vegetable consumption (Dijkstra & Elbert, 2019). Secondly, when prevention efforts focus on lowering SMU, then those with high SMU scores should be targeted, and according to the present study, these are not particularly defensive towards this message.…”
Section: Discussionmentioning
confidence: 96%
“…This study aimed to identify individual differences that predict defensive reactions towards persuasive information regarding SMU. The general predictors may reveal to what extent the earlier findings on CSAI and self‐esteem in persuasion regarding fruit and vegetable consumption (Dijkstra & Elbert, 2019) can be conceptually replicated with regard to SMU. Replicating these findings would show the robustness and generalizability of the WMaP with its EMi research paradigm, as SMU may be regarded as basically different from fruit and vegetable consumption: Persuasion in SMU is about controlling the impulse to use social media by self‐control behaviours; it is about decreasing an existing, functional behaviour, which is not the case in fruit and vegetable consumption.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The more specific and concrete the incoming information, the easier the matching process to build a mental image. The mental image can then be used in decision making or problem solving (Dijkstra & Elbert, 2019). When confronted with a present outcome, only a limited matching process with the individual's long‐term memory is needed to build a mental image.…”
Section: Discussionmentioning
confidence: 99%
“…The typical reactions toward weak arguments are negative thoughts, at least, in people for whom the topic is of personal relevance (Petty and Cacioppo, 1986 ; Dijkstra and Ballast, 2012 ). These negative thoughts are manifestations of defensive self-regulatory reactions that lower persuasion to cope with threat-related emotions (Dijkstra and Elbert, 2019 ). Also, in reaction to a persuasive message advocating lower meat consumption such defensive reactions have been traced (Piazza et al, 2015 ), also in psychophysiology (Spelt et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%